EP.TH.386Management of acute gallstone-related complications at Great Western Hospital. (28th October 2021) - Castelhano, Rute; Bartlett, Jessica; Wooler, Harry; Mahmoud, Ahmed; Theofilis, Aris; Shamali, Awad
Abstract: Aim: Gallstone-related disease accounts for a third of the admissions to the Surgical Department. In June 2019, an audit was undertaken at Great Western Hospital assessing the number of patients who underwent cholecystectomy, following initial diagnosis, in accordance to current guidelines. The results demonstrated a very low number of patients had cholecystectomy, within the targeted timeframe, which led to the implementation of a dedicated operative "hot gallbladder" list weekly. In June 2020, we re-audit the service to evaluate the impact of the change implemented. Methods: A retrospective observational analysis of patients admitted to the Hospital in June 2020 with gallstone-related disease. Data was collected using the Surgical on-call lists, these were analysed and patients selected according to the reason for admission. Only gallstone related issues were considered in this analysis. Finally, via Medway, the time from admission to surgery was assessed. Results: Despite the disruption in service provision due to COVID-19, the implementation of the "hot gallbladder" list led to a 10.7% increase in timely cholecystectomies, bringing the overall compliance to 14%. There was also a significant reduction in biliary related re-admissions, from 58% to 37%. Despite 47.3% of patients were still awaiting surgery, the waiting list was reduced by 5.2% in only 1 year. Conclusions: This study demonstrated that the implementation of the "hot gallbladder" list has improved the compliance with the current guidelines. The change has brought us in line with the national average of 15%, as estimated by RCSEng, therefore demonstrating the efficacy of the weekly list.